Comparative 14C and OSL dating of loess-paleosol sequences to evaluate post-depositional contamination of n-alkane biomarkers. Issue 1 (6th February 2017) - Zech, Michael; Kreutzer, Sebastian; Zech, Roland; Goslar, Tomasz; Meszner, Sascha; McIntyre, Cameron; Häggi, Christoph; Eglinton, Timothy; Faust, Dominik; Fuchs, Markus
Abstract: There is an ongoing controversial discussion as to whether n- alkane lipid biomarkers—and organic matter of loess in general—reflect a synsedimentary paleoenvironmental/climate signal or whether they are significantly affected by postdepositional "contamination, " for example related to root and rhizomicrobial activity. In order to address this issue at our study site (the Middle to Late Weichselian loess-paleosol sequence Gleina in Saxony, Germany), we determined and compared radiocarbon ages of bulk n -alkanes and sedimentation ages, as assessed by optically stimulated luminescence (OSL) dating. The bulk n -alkanes of the four dated samples yielded calibrated 14 C ages ranging from 24.1 to 49.7 cal ka BP (95.4% probability ranges). While the three uppermost n -alkane samples are well within the range or even slightly older than the OSL-inferred sedimentation ages, the lowermost n -alkane sample is slightly younger than the OSL ages. There is hence little or no evidence at our study site for n -alkanes in loess-paleosol sequences being significantly "contaminated" by deep subsoil rooting or microbial processes. We propose a 14 C isotope mass balance calculation for estimating such contaminations quantitatively. Radiocarbon dating of bulk n -alkanes might have great potential for Quaternary research, and we encourage further comparative 14 C and OSL studies.